(untitled) - Jack C Richards (New York, 1997)
The book provides comprehensive suggestions for the most effective ways of presenting and exploiting the activities in the Student Book. The step-by-step notes provides both novice and experienced teachers practical guidance for classroom teaching. It also offers suggestions for working with large and mixed ability classes and on how best to exploit the Project File and Glossary.
Keywords: english language - listening english - problems, exercises, etc,english language - spoken english - problems, exercises, etc,english language - textbooks for foreign speakers